Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2001
DOI: 10.3136/fstr.7.154
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Flavonoids on the Differentiation of 3T3-L1 Adipocytes.

Abstract: The effect of dietary flavonoids (flavone, isoflavone, flavanone, chalcone, flavonol, and flavonol derivatives) on the differentiation of 3T3-L1 adipocytes was investigated. Glycerol-3-phosphate dehydrogenase (GPDH) activity, which is a hallmark of 3T3-L1 differentiation, was measured. The GPDH activity in the cells treated with quercetin, kaempferol, and isorhamnetin was significantly lower than that in the control cells. A low lipid accumulation in cells stained with Oil-Red O was observed following treatmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
14
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 23 publications
1
14
0
Order By: Relevance
“…Further studies will be needed to determine the mechanism and the relation of the chemical structure of the fl avonoids and the activity. Interestingly, some fl avonoids such as quercetin, kaempferol, isorhamnetin have also been reported as having antiadipogenesis activity (Iwashita et al, 2001). …”
Section: Discussionmentioning
confidence: 98%
“…Further studies will be needed to determine the mechanism and the relation of the chemical structure of the fl avonoids and the activity. Interestingly, some fl avonoids such as quercetin, kaempferol, isorhamnetin have also been reported as having antiadipogenesis activity (Iwashita et al, 2001). …”
Section: Discussionmentioning
confidence: 98%
“…The authors suggested the antidifferentiation by quercetin to be the direct inhibition of glyceraldehyde‐3‐phosphate dehydrogenase, the key enzyme in lipid synthesis. Other flavonoids that have been reported to have inhibiting effects were naringenin, hesperetin and phloretin (Iwashita et al . 2001).…”
Section: Resultsmentioning
confidence: 99%
“…These compounds included the six flavonols, quercetin (5), 25) isorhamnetin (6), 26) rhamnetin (7), 27) quercitrin (8), 25) kaempferol (9), 25) and afzelein (10), 28) the five flavons, chrysoeriol (11), 29) apigenin (12), 30) tricin (13), 31) luteolin (14), 32) and amentoflavone (15), 33) the flavanonol, taxifolin (16), 34) the chalcone, isoliquiritigenin (17), 35) the dithiodicarboxylic acid, 3,3′-dithiodipropanoic acid (18), 36) the indole derivative, indole-3-carboxylic acid (19), 37) the alloxazine derivative, 7,8-dimethylalloxazine (20), 38) the phenylpropanoid, (E)-p-coumaric acid (21), 39) and the mono-terpenoid, (6S)-menthiafolic acid (22). 40) Compounds 6, 7, 11-22 were isolated for the first time from the flower of A. julibrissin.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, natural products also have been reported as a subject for an obesity study in 3T3-L1 cells. Previously, quercetin, 19,20) berberine, 21) ginsenosides, 22) and curcumin, 23) on lipid accumulation in 3T3-L1 adipocytes was investigated. Consequently, crude drugs and natural products with similar properties would help to solve obesity problems worldwide.…”
mentioning
confidence: 99%